Oxidative-Induced Angiogenesis Is Modulated by Small Extracellular Vesicle miR-302a-3p Cargo in Retinal Pigment Epithelium Cells - Maria Oltra; Miriam Martínez-Santos; María Ybarra; Hugo Rowland; María Muriach; Javier Romero; Javier Sancho-Pelluz; Jorge M. Barcia (Antioxidants, 2022)
Extracellular vesicles are released from cells under diverse conditions. Widely studied in cancer, they are associated with different diseases playing major roles. Recent reports indicate that oxidative damage promotes the release of small extracellular vesicle (sEVs) from the retinal pigment epithelium (RPE), with an angiogenic outcome and changes in micro-RNA (miRNA) levels. The aim of this study was to determine the role of the miRNA miR-302a-3p, included within RPE-released sEVs, as an angiogenic regulator in cultures of endothelial cells (HUVEC). ARPE-19 cell cultures, treated with H2O2 to cause an oxidative insult, were transfected with a miR-302a-3p mimic. Later, sEVs from the medium were isolated and added into HUVEC or ARPE-19 cultures. sEVs from ARPE-19 cells under oxidative damage presented a decrease of miR-302a-3p levels and exhibited proangiogenic properties. In contrast, sEVs from miR-302a-3p-mimic transfected cells resulted in control angiogenic levels. The results herein indicate that miR-302a-3p contained in sEVs can modify VEGFA mRNA expression levels as part of its antiangiogenic features.